Morphometric Study of the Styloid Process of Temporal Bone - Patil, Sachin (J Clin Diagn Res, 2014)
Objective: Styloid process of temporal bone is clinically important, because variations in length, as well as the angulations of styloid process are associated with the symptoms of stylalgia (Eagle’s syndrome) and the surgical excision of the process could alleviate neck and cervicofacial pain in patients. This study was aimed to evaluate the length, angulation and distance between bases and tips of the styloid process. Materials and Methods: We studied 114 dry skull bones with intact styloid processes. The length of styloid process and distance between bases and tips of the styloid process were measured with the help of vernier calipers. The angulation (anterior and medial angles) of the styloid process was measured directly from the digital images by the image analysis using Adobe Photoshop 7.0 and Image Tool 3.0 Program. A styloid process longer than 3 cm was identified as an elongated styloid process. Results: The means of length of styloid process, distance between bases and tips of styloid process were 2.58 cm, 6.80 cm and 4.65 cm respectively, while means of anterior and medial angles were 62.45(o) and 74.15(o), respectively. Significant statistical difference was seen in anterior angles between groups with normal and elongated styloid processes (p>0.001). Conclusion: Anterior angulation and distance between bases and tips decreased in elongated styloid processes while medial angulation showed no significant change. Our findings highlight the importance of the examination of styloid process in patients with symptoms of stylalgia.